Cultural and micropolitical interactions of teacher relations - Tabancali, Erkan; Ongel, Gulay (EDUCATION ASSOC SOUTH AFRICA, 2024)
With the research discussed in this article we aimed to investigate the social-relational factors that negatively affect teacher relations. For this purpose, the perceptions that teachers have towards their relations, and especially collaboration, were investigated from micropolitical and cultural perspectives using a qualitative approach and a phenomenology model. Data were analysed using content analysis. Semi-structured interviews were conducted with 60 teachers in T & uuml;rkiye to explore their thoughts on teacher relations. The findings shed light on micropolitical strategies that negatively affect teacher relationships. In addition, findings provide empirical data from micropolitical and cultural frameworks on theoretical and applied strategies that facilitate approaches and practices to improve teachers' collaborative relationships.
Keywords: collaboration; micropolitics; professional development; school improvement; teacher relations; STUDENT-ACHIEVEMENT; JOB-SATISFACTION; SELF-EFFICACY; COMMUNITY; PERCEPTIONS; PERSPECTIVE; IMPROVEMENT; LEADERSHIP; EMOTIONS; Education & Educational Research